Land Cover Mapping Using High Spatial Resolution SPOT Data Over Penang Island Malaysia. - Lim, H. S.; MatJafri, M.Z.; Abdullah, K.; Mohd. Saleh, N.; Teh, H. T.; Mustapha @ Rosli, M. R. (2009)
Satellite digital imagery has proved to be an effective tool for land cover changes studies. The objective of this study is to demonstrate the effectiveness of SPOT imageries in changes detection over Penang Island, Malaysia. An understanding of land use/land cover at local with high resolution is important to prepare the latest data and can be used in many purposes. The neural network classifier was performed to the satellite images and the results were compared with four standard supervised classification techniques, such as the maximum likelihood, minimum distance-to-mean and parallelepiped.